Technological innovation systems in contexts: Conceptualizing contextual structures and interaction dynamics - Bergek, Anna; Hekkert, Marko; Jacobsson, Staffan; Markard, Jochen; Sandén, Björn; Truffer, Bernhard (Elsevier BV, 2015)
This paper addresses interactions between technological innovation systems (TIS) and wider "context structures". While TIS studies have always considered various kinds of contextual influences, we suggest that the TIS framework can be further strengthened by a more elaborated conceptualization of TIS context structures and TIS-context interactions. For that purpose, we identify and discuss four especially important types of context structures: technological, sectorial, geographical and political. For each of these, we provide examples of different ways in which context structures can interact with a focal TIS and how our understanding of TIS dynamics is enhanced by considering them explicitly. Lessons for analysts are given and a research agenda is outlined.
Keywords: Context; Geography; Politics; Sector; Technological innovation system; Transition; Taverne; Renewable Energy, Sustainability and the Environment; Environmental Science (miscellaneous); Social Sciences (miscellaneous); SDG 7 - Affordable and Clean Energy